Waldenström’s Macroglobulinemia Masquerading as Birdshot Chorioretinopathy - Kim, Jane S. (Retin Cases Brief Rep, 2017)
PURPOSE: To describe Waldenström’s macroglobulinemia (WM) as a masquerade syndrome. METHOD: Case report. RESULTS: A 59-year-old human leukocyte antigen (HLA)-A29-negative Caucasian male presented with a seven-year history of floaters, progressive vision loss, and poor contrast sensitivity along with choroidal lesions suggestive of birdshot chorioretinopathy (BCR). Fluorescein angiography, fundus autofluorescence, and indocyanine green angiography showed multiple areas of hyperfluorescence and hypofluorescence. Electroretinography showed reduced cone and rod responses. Comprehensive work-up for infectious, paraneoplastic, and other causes including sarcoidosis was negative at the time. The patient was treated with multiple immunomodulatory agents without any significant improvement. Two years after initial presentation, the patient developed normocytic anemia and high levels of inflammatory markers. Further work-up yielded a diagnosis of WM. His choroidal lesions were significantly reduced after treatment with rituximab and bendamustine. CONCLUSION: We report a case of WM masquerading as BCR. Other indolent diseases should be considered in the differential diagnosis for HLA-A29-negative patients presenting with birdshot-like lesions, especially if they are clinically unresponsive to multiple systemic immunosuppressive agents.